Plasma Proteome Alterations of Laying Hens Subjected to Heat Stress and Fed a Diet Supplemented with Pequi Oil (Caryocar brasiliense Camb.): New Insights in the Identification of Heat Stress Biomarkers - da Silva, Joyce [UNESP]; Andrade, Luane [UNESP]; Rodrigues, Paola [UNESP]; Cordeiro, Laís [UNESP]; Lima, Gabrieli [UNESP]; Lopes, Júlia [UNESP]; Castillo, Elis [UNESP]; Martins, Renata [UNESP]; Assunção, Andrey [UNESP]; Vieira, José [UNESP]; Busalaf, Marília; Adamec, Jiri; et al. (MDPI, 2024)
Heat stress can disrupt the balance between the heat poultry release into the environment and the heat they generate. Pequi oil has antioxidant properties, which may mitigate the heat stress effects. This study aimed to investigate the response of laying hens to pequi oil supplementation under heat stress using a proteomic approach. A total of 96 Lohmann White laying hens with 26 weeks old were housed in a completely randomized design with a 2 × 2 factorial arrangement. They were housed in two climate chambers, thermal comfort temperature ± 24.04 °C with the relative humidity ± 66.35 and heat stress (HS) ± 31.26 °C with the relative humidity ± 60.62. They were fed two diets: a control diet (CON), basal diet (BD) without additives, and with Pequi oil (PO), BD + 0.6% PO. After 84 days, plasma samples were analyzed using Shotgun and LC-MS/MS. Proteins related to anti-inflammation, transport, and the immune system were differentially expressed in hens fed PO and CON under heat stress compared to those in thermoneutral environments. This helps protect against oxidative stress and may support the body’s ability to manage heat-induced damage, stabilizing protein expression under stress conditions. The ovotransferrin proteins, fibrinogen isoforms, apolipoprotein A-I, Proteasome activator subunit 4, Transthyretin, and the enzyme serine Peptidase Inhibitor_Kazal Type 5, which presented Upregulated (Up) equal to 1, present characteristics that may be crucial for enhancing the adaptive responses of hens to thermal stress, thereby increasing their tolerance and minimizing the negative effects of heat on egg production. The data presented in this manuscript provides new insights into the plasma proteome alterations of laying hens fed a diet supplemented with pequi oil during heat stress challenges.
Keywords: antioxidant compounds; oxidative stress; phytogenics; poultry; shotgun–LC-MS/MS